A Dynamic Ice-structure Interaction Model for Prediction of Ice-induced Vibration - Wu, Tianyu; Qiu, Wenliang (Periodica Polytechnica Civil Engineering, 2019)
Sea ice crashing against offshore structures can cause strong ice-induced vibration and have a major impact on offshore structural safety and serviceability. This paper describes a numerical method for the prediction of ice-induced vibration when a vertical offshore structure is subjected to the impact of sea ice. In this approach, negative damping theory and fracture length theory are combined and, along with ice strength-stress rate curve and ice failure length, are coupled to model the internal fluctuating nature of ice load. Considering the elastic deformation of ice and the effect of non-simultaneous crushing failure of local contact between ice and structures, the present ice-induced vibration model is established, and the general features of the interaction process are captured. To verify its efficacy, the presented simulation methodology is subjected to a model test and two full-scale measurements based on referenced studies. Example calculations show good agreement with the results of the model test and full-scale measurements, which directly indicates the validity of the proposed simulation method. In addition, the numerical simulation method can be used in connection with FE programs to perform ice-induced vibration analysis of offshore structures.